Multicenter performance evaluation and reference range determination of a new one‐stage factor VIII assay. Issue 4 (11th March 2022) - Lowe, Anna E.; Jones, Robert; Kitchen, Steve; Geisen, Ulrich; Rozsnyai, Gergely; Jilma, Petra; Quehenberger, Peter
Abstract: Introduction: We conducted a multicenter evaluation of a new one‐stage factor VIII (FVIII) assay (Roche Diagnostics), intended for the quantitative assessment of FVIII activity. We evaluated the analytical performance of the FVIII assay on the cobas t 711 analyzer. Methods: Experiments performed at three laboratories used 3.2% citrated residual or commercially purchased plasma samples. Five human plasma pools and two controls were used to determine assay within‐run and within‐laboratory precision, and total reproducibility; coefficients of variation (CVs) and/or standard deviations (SDs) were calculated. Lot‐to‐lot variability and method comparison (vs Coagulation FVIII Deficient Plasma/Dade Actin FS Activated PTT reagent/Standard Human Plasma Calibrator on the Sysmex CS‐5100 analyzer; Siemens Healthineers) were evaluated by Passing–Bablok and Deming regression, respectively, and Pearson's r calculated. Assay‐specific reference range was determined using 199 fresh plasma samples from healthy adults, not receiving anticoagulants. Results: Across sites, SDs for repeatability were 0.016–0.046 for samples with ≤1.0 international units (IU)/dL FVIII activity; CVs were 0.9%–3.8% for samples with >1.0 IU/dl activity. Among samples with mean FVIII activity 0.344–133 IU/dl, good intermediate precision (SD 0.020 for samples with 0.344 IU/dl activity; CV 1.8%–4.7%) and good total reproducibility (CV 2.0%–13.3%) were observed. The FVIII assay showed excellent lot‐to‐lot variability (Pearson's r  = .999) and good correlation with the comparator assay (Pearson's r  = .993–.996). The reference range for FVIII activity was 82.2−218.0 IU/dl. Conclusion: The one‐stage FVIII assay demonstrated robust analytical performance on the cobas t 711 analyzer, supporting its use in routine laboratory practice. Abstract : We conducted a multicenter evaluation of a new one‐stage factor VIII (FVIII) assay (Roche Diagnostics), intended for the quantitative assessment of FVIII activity. The new one‐stage FVIII assay demonstrated robust analytical performance on the cobas t 711 analyzer, supporting its use in routine laboratory practice.